Etične dileme pri rehabilitaciji bolnikov po nezgodni poškodbi glave - Grabljevec, Klemen (Rehabilitacija (Ljubljana), 2017)
Acute treatment and medical rehabilitation of patients after traumatic brain injury are an endless source of ethical dilemmas and questions. Ethical considerations in rehabilitation after traumatic brain injury are undoubtedly overlapping with ethical considerations in rehabilitation of other chronic neurologic conditions, but there are some additional factors involved as a result of specific combinations of psycho-social and clinical consequences after traumatic brain injury. Ethical dilemmas arise throughout the rehabilitation process and continue after discharge of the patient in the local environment. Ethical issues arising during rehabilitation potential assessment, rehabilitation in sub-optimal conditions and during transition of the patient to the local environment after rehabilitation are described in the paper.
Keywords: Brain Injuries; ethical issues; Ethics; etične dileme; nezgodna možganska poškodba; poškodbe glave; rehabilitacija; rehabilitation; traumatic brain injury; vocational rehabilitation